Involvement of Neural Transient Receptor Potential Channels in Peripheral Inflammation - Silverman, Harold A.; Chen, Adrian; Kravatz, Nigel L.; Chavan, Sangeeta S.; Chang, Eric H. (Frontiers in Immunology, 2020)
Transient receptor potential (TRP) channels are a superfamily of non-selective cation channels that act as polymodal sensors in many tissues throughout mammalian organisms. In the context of ion channels, they are unique for their broad diversity of activation mechanisms and their cation selectivity. TRP channels are involved in a diverse range of physiological processes including chemical sensing, nociception, and mediating cytokine release. They also play an important role in the regulation of inflammation through sensory function and the release of neuropeptides. In this review, we discuss the functional contribution of a subset of TRP channels (TRPV1, TRPV4, TRPM3, TRPM8, and TRPA1) that are involved in the body’s immune responses, particularly in relation to inflammation. We focus on these five TRP channels because, in addition to being expressed in many somatic cell types, these channels are also expressed on peripheral ganglia and nerves that innervate visceral organs and tissues throughout the body. Activation of these neural TRP channels enables crosstalk between neurons, immune cells, and epithelial cells to regulate a wide range of inflammatory actions. TRP channels act either through direct effects on cation levels or through indirect modulation of intracellular pathways to trigger pro- or anti-inflammatory mechanisms, depending on the inflammatory disease context. The expression of TRP channels on both neural and immune cells has made them an attractive drug target in diseases involving inflammation. Future work in this domain will likely yield important new pathways and therapies for the treatment of a broad range of disorders including colitis, dermatitis, sepsis, asthma, and pain.